Livestock farmer groups for innovation uptake, market access and policy influence in Mai Son District, Son La Province, Vietnam - Thinh, Nguyen Thi; Thanh, Lo Quang; Le, Pham Thi; Marshall, Karen; Atieno, Mary; Burkart, Stefan (International Livestock Research Institute, 2024)
The CGIAR Initiative on Sustainable Animal Productivity (SAPLING) has supported eight livestock farmer groups in Mai Son District, Son La Province, Vietnam, since 2023 as part of efforts to transform the region’s livestock sector. As of October 2024, the eight farmer groups had a total membership of 692 households, an increase from 127 households in October 2023. Among these, 208 households were represented by women, while 484 were represented by men. These groups have proven effective in promoting and implementing technical innovations and served as role models for other livestock farmers in their communities. One thousand seven hundred (1,700) farmers have attended the groups’ information sharing sessions in the eight key villages where these groups operate. More than 900 farmers engaged in an online Zalo platform, which the farmer groups utilized to deliver training materials on SAPLING’s innovations and to provide ongoing support for farmers via the platform. The groups also established eight livestock demonstration farms serving as hands-on learning resources for both members and non-members. With the support of the farmer groups, 692 smallholder households have been recorded as adopting at least one of SAPLING’s innovations (i.e., AI, feeds and forages, or animal health), benefiting approximately 3,321 farmers when factoring in an average household size of 4.8 persons.